PHYSIOLOGICAL RESPONSE OF INDIAN MUSTARD (BRASSICA JUNCEA L.) TO DIFFERENT MOISTURE REGIMES - SUKHMANINDER KAUR,; PUSHP SHARMA, (The Bioscan, 2015)
Drought is undoubtedly one of the most important environmental stresses limiting the productivity of crop plants in the arid and semiarid areas of world. The study was carried out during two winter seasons (2009-10 and 2010- 11) to investigate the effects of water deficit on leaf water status in terms of RWC and water potential, SPAD chlorophyll, stomatal frequency and different components of chlorophyll fluorescence during different stages of crop growth with drought susceptibility (DSI) and tolerance indices (DTI). Physiological traits were highest at 65DAS and moisture stress reduced SPAD values by 6.1% and 8.6% and RWC by 11.5% and 12.6% at 90 and 120DAS respectively. Profound impact of moisture deficit was to the tune of 52.3% on the mean water splitting capacity on the donor side of PSII (inferred by Fv/Fo) while photochemical efficiency (PSII) was reduced by 4.3% in the B. juncea genotypes. Stomatal frequency was higher on the abaxial side. Seed yield (SY) was positively associated with SPAD (0.318) and RWC (0.266) at 90DAS, stomatal size (0.265), Fv/Fo (0.106) and DTI1 (0.429) and DSI3 (0.574*), though the magnitude of association was low under moisture stress. High yielding cultivars under moisture stress i.e NPJ-79, NLM-3 and PLM-2 showed comparatively lesser reduction in SPAD, RWC, water potential, disruption of PSII and also water splitting capacity on the donor side of PSII.